Spatial distribution of capitellidae (Annelida Polychaeta) in seagrass beds of Palompon, Leyte in relation to sediment granulometry - De Los Santos, Cherie Gil F. (2016.)
Polychaetes which include the capitellids acts as an important component of coastal ecosystem. They play an important role in linking the primary producers (e.g. seagrass) to higher trophic levels. This study was conducted to determine the spatial distribution of Family Capitellidae in seagrass beds of Palompon, Leyte specifically, to determine the taxonomic composition and abundance of capitellids and relate their distribution with sediment characteristics of the area. This is the first study in the country focusing only to the Family Capitellidae. Five stations were established in the study site with three replicates each. NaGISA (National Geography in Shore Areas) sampling protocol was used in this study which is a global program that aims to monitor the biodiversity of the world coastal zones and the changes in it overtime. The study site was a low energy area and composed mainly of coarse sand due to the seagrasses that buffer wave action resulting to less resuspension and mixing of sediments. An overall mean density of 388.6 ind.?m-2 was recorded with a total of 103 individuals belonging to 13 species and 7 genera of Family Capitellidae. Capitellidae showed a positive relationship with fine sand even though the area was composed mainly of coarse sand. Fine sediment has the ability to increase food availability by accumulating organic matter. Station 1 exhibited the highest species abundance and this might be due to the location of the station wherein there was a high possibility of high organic content in the area. This was further supported by the high abundance of Capitellacapitata in this station. This species prefers fine sediment with high organic content and this was also the dominant species of this study. However, Station 4 with the highest percentage of silt and fine sediments showed high capitellid density and diversity. Fine sediments present a larger available surface for adhesion of organic particles that is why capitellids proliferate in this type of sediment. The results indicated that sediment granulometry greatly affects the composition, abundance and distribution of the capitellids in the area.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Capitellidae; Sediment Characteristics; Seagrass; Capitella Capitata; Palompon, Leyte